Validation of a maximal incremental skating test performed on a slide board: Comparison with treadmill skating - Piucco, T.; Diefenthaeler, F.; Soares, R.; Murias, J. M.; Millet, G. Y. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the criterion validity of a maximal incremental skating test performed on a slide board (SB). Methods: Twelve subelite speed skaters performed a maximal skating test on a treadmill and on a SB. Gas exchange threshold (GET), respiratory compensation point (RCP), and maximal variables were determined. Results: Oxygen uptake (VO 2) (31.0±3.2 and 31.4±4.1 mL/min·kg), percentage of maximal VO2 (VO2 max) (66.3±4 and 67.7±7.1%), HR (153±14 and 150±12 bpm), and ventilation (59.8±11.8 and 57.0±10.7 L/min) at GET, and VO2 (42.5±4.4 and 42.9±4.8 mL/min·kg), percentage of VO2 max (91.1±3.3 and 92.4±2.1%), heart rate (HR) (178±9 and 178±6 bpm), and ventilation (96.5±19.2 and 92.1±12.7 L/min) at RCP were not different between skating on a treadmill and on a SB. V O2 max (46.7±4.4 vs 46.4±6.1 mL/min·kg) and maximal HR (195±6 vs 196±10 bpm) were not significantly different and correlated (r=.80 and r=.87, respectively; P<.05) between the treadmill and SB. VO2 at GET, RCP, and VO2 max obtained on a SB were correlated (r>.8) with athletes` best times on 1500 m. Conclusions: The incremental skating test on a SB was capable to distinguish maximal (VO2 and HR) and submaximal (VO2, % VO2 max, HR, and ventilation) parameters known to determine endurance performance. Therefore, the SB test can be considered as a specific and practical alternative to evaluate speed skaters.